A theory of international strategic judicial dialogue: Convergence and Divergence between the Court of Justice of the European Union and the European Court of Human Rights - Plan, Audrey Mathilde (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2024)
International Courts interact with each other, especially by referring to each other's rulings, and the consequences of these interactions often assumed to be a progressive and stable convergence of their respective jurisprudence. The Court of Justice of the European Union (CJEU) and the European Court of Human Rights (ECtHR), with their overlapping jurisdictions, are engaged in such interactions. However, rather than a stable convergence, their jurisprudence displays both convergence and divergence, with changes through time within different issue-areas. How can we causally explain this variation in convergence and divergence between the CJEU and ECtHR? This project will explain these different patterns, so far unexplored, by proving that the CJEU and the ECtHR engage strategically with each other to safeguard their authority as policymakers within the European judicial and institutional system. This research relies on three qualitative longitudinal case studies across time in three different issue-areas: the right to privacy of companies, exceptions to the execution of European Arrest Warrants, and the right to Legal Gender Recognition. Using process tracing and triangulation with data from diverse sources, including interviews with current and former CJEU and ECtHR judges, it traces the evolution of the convergence and divergence of both Courts on this question and reconstructs the causal pathways leading to this variation. The results support the theory that overlapping International Courts use convergence with each other as a legitimacy-enhancing mechanism, in reaction to threats from relevant actors: domestic courts, governments, but also the other European Court. The contribution of this dissertation is two-fold: first, it presents a novel method to empirically and systematically evaluate the degree to which two international courts converge or diverge with each other. Second, it shows that overlaps in the jurisdictions of International Courts, a situation becoming ever more common due to the increased judicialization of International Law, present these Courts with both new challenges, and new opportunities to reinforce their authority.
APPROVED
Keywords: International Courts; Human Rights; Court of Justice of the European Union; Interdisciplinarity; Qualitative Methods; European Court of Human Rights